Rancang Bangun Aplikasi Pengelolaan Bahan Baku Kafe Menggunakan Metode Analytical Hierarchy Process (AHP) dan Push Notification - Julita Gandasari Ariana; Aryo Pinandito; Muhammad Tanzil Furqon (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
To maintain quality of service, a café must pay attention to several aspect. One of them is the availability of the menu served by the café. The availability of the menu also depends on the availability of the ingredients needed to make it. Therefore, the café manager need to make sure that the ingredients is enough and resupplied fast enough when needed. Push Notification is a technology which allow information to be delivered to stakeholder via instant alert on their smartphone. This concept can be used by café manager to monitor the availability of ingredients, so that any insufficient ingredients can be resupplied fast. Analyical Hierarch Process (AHP) is used to determine the priority of ingredients that needed to be resupplied first. Ingredient stock, the number of menu using corresponding ingredient, and ingredient price are used to determine supply priority. The result of using both method reach 68% in accuracy, and 80% in delivery rate of push notification.